Efektvitas Media Kartu Huruf terhadap Kemampuan Membaca Siswa Kelas II Sekolah Dasar - Listia Fitriyawati; Ruwet Rusiyono (Alma Ata University Press, 2026)
Reading is a means for students to expand their knowledge. This research is motivated by the low reading ability of students in Indonesia. This issue is evidenced by the 2023 education report card of SD N Bantulan, which scored 66.67% (moderate achievement), as well as the minimal utilization of innovative learning media by teachers. This study aims to determine the eﬀectiveness of letter card media on the reading ability of second-grade students at SD N Bantulan. This quantitative research implemented an experimental method with a quasi-experimental design. The research subjects consisted of 40 second-grade students at SD N Bantulan and 2 classroom teachers. The research design utilized a pretest-posttest format, comparing the experimental class and the control class through a test instrument. Statistical analysis of the data was performed using the paired samples t-test assisted by IBM SPSS 25 at a signiﬁcance level of 0.05. The results showed that the mean pretest score was 8.10 for the experimental class and 8.00 for the control class. After the treatment (posttest), the mean score of the experimental class increased to 18.35, while the control class reached 17.85. The hypothesis testing yielded a signiﬁcance value (2-tailed) of 0.000 < 0.05, leading to the acceptance of Ha and the rejection of Ho. It can be concluded that the use of letter card media provides positive and signiﬁcant eﬀectiveness in improving the reading ability of second-grade students at SD N Bantulan.